Tarif Pajak, Keadilan Pajak, Teknologi Informasi Terhadap Perilaku Penggelapan Pajak - Erlina Widayanti; Dian Sulistyorini Wulandari; Diah Ayu Prihasteti (Journal of Trends Economics and Accounting Research, 2023)
Taxes are among the most important element supporting the state revenue budget. The assumption that taxes are a burden causes taxpayers to always try to minimize the amount of tax payable that must be paid, and in achieving their wishes, they are prone to fraud such as tax evasion. The number of tax evasion cases in Indonesia will indirectly shape taxpayers' perceptions of tax evasion behavior. This study aims to examine the effect of tax rates, tax justice, technology, and information on tax evasion. The population in this study were all individual taxpayers registered at KPP Pratama Cikarang Selatan. The sampling technique used simple random sampling with a sample of 100 people. The primary data collection method used is the survey method, which involves distributing questionnaires. The analysis method used in this research is multiple linear regression analysis. The results of this study indicate that partial tax rates and tax justice have no effect on tax evasion. While technology and information affect tax evasion. Simultaneously, tax rates, tax justice, technology, and information affect tax evasion.